Teknik Pembelajaran Detik Smart Untuk Meningkatkan Keaktifan dan Keterampilan Pemeliharaan Mesin Kendaraan Ringan - Nanang Nurdiyanto (Universitas Muhammadiyah Magelang, 2020)
The purpose of this research is to increase the activeness and skills of maintaining light vehicle engines, using the Detik Smart (Membuat Video Praktik Dengan Smartphone). This research was conducted by students from August to November 2019, in class XII Automotive B (OB) SMK Negeri 1 Magelang in the odd semester 2019/2020 academic year. This study uses a classroom action method. Data collection techniques used observation sheets to obtain data about student activity. Meanwhile, to obtain data on the skills to maintain light vehicle engines, this study used theoretical and practical tests. The data analysis technique used is descriptive comparative followed by reflection. The research carried out in two cycles. Cycle I contains actions in the form of a teaching and learning process using the Detik Smart learning technique as a group, where one group collects 1 video. In cycle II, learning was perfected by a teaching and learning process using the Detiksmart learning technique individually, where each student collects 1 practical video. The results of the action show that the use of the Detik Smart method is able to increase the activeness of the practice of maintaining light vehicle engines. The class average score increased from the initial condition of 67% to 76% in the first cycle and to 83% in the second cycle. This score shows that the condition of the average activity of students increases from the less active to the active category. In addition, the use of the Detik Smart method was also able to improve the skills to maintain light vehicle engines. While the students' skill scores in the initial conditions were obtained at 73.20. After taking the action in the first cycle, the class average score increased to 78.75. Then in the second cycle it also rose to 81.30. The lowest value in the initial conditions is 40.25, increasing to 73.50. Meanwhile, the highest value in the initial conditions was 82.50, increasing to 91.50 in the second cycle.